Climate Change in APEC : Assessing Risks, Preparing Financial Markets, and Mobilizing Institutional Investors - World Bank (World Bank, Washington, DC, 2020)
The World Bank Group prepared this report, Climate Change in APEC: Assessing Risks, Preparing Financial Markets, and Mobilizing Institutional Investors to inform policymakers, financial sector regulators, and investors from across APEC member economies about the interconnected climate change challenges that they face. This report aims to help these stakeholders better understand the human and economic risks that climate change poses to the region and to provide them with a starting point for discussions about opportunities for action. This report outlines the potential human and economic impacts of climate change on APEC member economies and the benefits to mitigating these impacts. It then outlines the climate-related risks to financial institutions and how financial system regulators can help institutions to manage these risks. It concludes with a discussion of the policy, regulatory and market barriers to scaling-up institutional investors' contributions to climate finance and solutions to each. In doing so, this report aims to capitalize on the unique and exciting opportunity provided by the 2019 APEC Investor Forum for policymakers, financial sector regulators and investors from across APEC member economies to share insights on the interconnected climate change challenges that they face and to provide a starting point for discussions about opportunities for action.